Microwave synthesis of magnetically separable ZnFe2O4-reduced graphene oxide for wastewater treatment - Jumeri, F. A.; Lim, Hong Ngee; Ariffin, S. N.; Huang, Nay Ming; Teo, P. S.; S. O., Fatin; Chia, Chin Hua; Harrison, Ian (Elsevier, 2014)
A magnetically separable ZnFe2O4-reduced graphene oxide (rGO) nano-composite was synthesised via a microwave method. Field emission scanning electron microscopy images of the nano-composite showed a uniform dispersion of nanoparticles on the rGO sheets. The performance of the nano-composite in wastewater treatment was assessed by observing the decomposition of methylene blue. The nano-composite showed excellent bifunctionality, i.e. adsorption and photocatalytic degradation of methylene blue, for up to five cycles of water treatment when illuminated with light from a halogen bulb. In contrast, water treatment with the nano-composite without illumination and the illuminated rGO, with no decoration of nanoparticles, diminished significantly after the first treatment. The reclamation of the ZnFe2O4-rGO nano-composite from treated water could be easily achieved by applying an external magnetic field.